Rainfall Dependence of Hospital Visits of Aeromonas-Positive Diarrhoea - Hashizume, M.; Faruque, A.; Dewan, Ashraf (Springer Geography, 2013)
The numbers of patients with cholera and Aeromonas-positive diarrhoea show similar bimodal seasonality in Dhaka, Bangladesh. Considering the association between these two pathogens, our previous finding that the number of cholera cases increased following the period of high rainfall led us to investigate the potential role of rainfall on the transmission of Aeromonas-positive diarrhoea. This study quantifies the impact of rainfall on the number of cases of Aeromonas-positive diarrhoea, to gain a deeper insight into the mechanisms of the seasonality of the disease. We examined a time series of the number of hospital visits due to Aeromonas-positive diarrhoea per week in relation to weekly rainfall from 1996 to 2000, using Poisson regression models and adjusting for seasonal and between-year variation, public holidays and temperature. The weekly number of cholera cases increased by 20.7 % (95 % confidence interval, 10.6–31.6) for a 10-mm increase in average rainfall over lags of 0–16 weeks. There was no clear relationship between the number of cases and river level or temperature.